Analisis Prediksi Potensi Akuifer dengan Metode Geolistrik Resistivitas Sounding (Studi Kasus di Kabupaten Mojokerto) - Abid, Luthfil; Nugroho, Laksono Djoko; Sajiyo, Sajiyo (Jurnal Spesialis Teknik Sipil (JSpTS), 2025)
Water usage from year to year continues to increase. It is caused by the growth of the population that is growing rapidly. This condition is inversely proportional to the increasingly limited availability of water sources. By because it's, required a study of potential water the soil in each area. The purpose of this study is nterpretation of the data resistivity geoelectric sounding using software IP2WIN to know the predictions of potential aquifers in the village of Sumberwuluh District of Dawarblandong Regency Mojokerto. Interpreting the data resistivity geoelectric sounding using software RES2DINV to know the predictions of potential aquifers in the village of Sumberwuluh District of Dawarblandong Regency Mojokerto. Evaluate the results of comparisons between IP2WIN and RES2DINV software. The method that is used in research this is the software IP2WIN and RES2DINV. Results of the study show that based on data processing IP2WIN software shows one layer of rock. Layers with apparent resistivity (ρ) = 68,5 Ω m, thickness (h) = 0,758 m and depth (d) = 0,758 m. With a depth of 0,758 m, it is predicted that only infiltration water and not potential as an aquifer. Based on data processing RES2DINV software shows a resistivity value of 1,75 - 35 Ω m. Resitivity value 1,75 – 4,12 Ω m is a layer with soil water content in blue contour color. Depth reaches 70.7 to 85.4 with a color contour of blue which is estimated to water the ground and potentially as aquifers. Evaluation of the results of the comparison processing of the data between software IP2WIN with RES2DINV indicate that the software RES2DINV much better in predicting the potential of the aquifer.